Inhibition of Resistance-Refractory P. falciparum Kinase PKG Delivers Prophylactic, Blood Stage, and Transmission-Blocking Antiplasmodial Activity. Issue 7 (16th July 2020) - Vanaerschot, Manu; Murithi, James M.; Pasaje, Charisse Flerida A.; Ghidelli-Disse, Sonja; Dwomoh, Louis; Bird, Megan; Spottiswoode, Natasha; Mittal, Nimisha; Arendse, Lauren B.; Owen, Edward S.; Wicht, Kathryn J.; Siciliano, Giulia; et al.
Summary: The search for antimalarial chemotypes with modes of action unrelated to existing drugs has intensified with the recent failure of first-line therapies across Southeast Asia. Here, we show that the trisubstituted imidazole MMV030084 potently inhibits hepatocyte invasion by Plasmodium sporozoites, merozoite egress from asexual blood stage schizonts, and male gamete exflagellation. Metabolomic, phosphoproteomic, and chemoproteomic studies, validated with conditional knockdown parasites, molecular docking, and recombinant kinase assays, identified cGMP-dependent protein kinase (PKG) as the primary target of MMV030084. PKG is known to play essential roles in Plasmodium invasion of and egress from host cells, matching MMV030084's activity profile. Resistance selections and gene editing identified tyrosine kinase-like protein 3 as a low-level resistance mediator for PKG inhibitors, while PKG itself never mutated under pressure. These studies highlight PKG as a resistance-refractory antimalarial target throughout the Plasmodium life cycle and promote MMV030084 as a promising Plasmodium PKG-targeting chemotype. Graphical Abstract: Highlights: MMV030084 inhibits P. falciparum liver and asexual blood stages and male gametes Proteomic and conditional knockdown studies identified PfPKG as the target Resistance selection studies identified TKL3 as a low-level resistance mediator PKG is a promising resistance-refractory target for antimalarial drug development Abstract : Vanaerschot et al. report an antimalarial, MMV030084, with potent antiplasmodial activity against all stages of human infection by Plasmodium falciparum . Metabolomic, phosphoproteomic, chemoproteomic, and gene-editing studies identified cGMP-dependent protein kinase (PKG) as the primary target, which did not mutate under selective drug pressure.